Міграції населення Північного Лівобережжя України до Східного Закубання у другій чверті ХІХ ст. - Герасимчук, О.М. (Сіверщина в історії України, 2023)
У статті висвітлюється перебіг міграційних рухів українців Північного Лівобережжя до Східного Закубання у другій чверті ХІХ ст. Детально аналізуються труднощі переселення й особливості адаптації мігрантів до умов життя на новій території. The article highlights the course of migration movements of Ukrainians from the Northern Left Bank to Trans-Kubania regions in the second quarter of the 19th century. The difficulties of resettlement and the peculiarities of adaptation of migrants to living conditions in the new territory are analyzed in detail. The methodological basis of this research is the principles of historicism, scientificity and objectivity, which contributed to the achievement of impartiality and reliability in clarifying specific facts and showing the logic of changes in the historical process. The scientific novelty of the research is that the course of the migration of the population of the Left Bank of Ukraine to Eastern Trans-Kubania in the second quarter of the XIX century and the consequences of this resettlement were first studied. Based on the processed materials we can draw the following conclusions. Ukrainian settlers, overcoming all difficulties, contributed to population growth and intensive economic development of Trans-Kubania regions, while ensuring the protection of the southern borders of the Russian Empire. Since then, a Ukrainian ethnic group has been formed here, based on former Zaporizhzhya Cossacks and peasants from Ukraine, mainly from Chernihiv, Poltava, Kharkiv regions. The attempt to unite Russians and Ukrainians in new villages led to the separation of these ethnic groups, which left its mark on the way of life and culture in these settlements for a long time.